Out of the dust - Hesse, Karen (New York : Scholastic, 1997)
In a series of poems, fifteen-year-old Billie Jo relates the hardships of living on her family's wheat farm in Oklahoma during the dust bowl years of the Depression.
Newbery Medal, 1998.
Keywords: Novels in verse; Dust Bowl Era, 1931-1939 -- Fiction; Farm life -- Oklahoma -- Fiction; Depressions -- 1929 -- Fiction; Poetry -- Fiction; Oklahoma -- History -- 20th century -- Fiction